Arabic Script In Banjarese Ethno-Religious Identity - Saifuddin Ahmad Husin (Jurnal Al-Maqoyis, 2022)
Language sociologists propose some factors contributing to the choice of a language over the other. These factors include economic, social, political, educational, and demographic factors. Other language scientists mention religious, values and attitudinal factors. What is real choice is there for those who use lesser-used script, such as Arabic script for Malay and Bahasa Indonesia, in a community where most people use a major national script, i.e. Latin script to write their language. How do economic, political, religious, educational, and demographic factors influence the choice of use of script for a language?